Modelling of experimental drying kinetics of Codiaeum Variegatum Brilliantissima-Zanzibar used as a corrosion inhibitor - Vincent, Izionworu Onuegbu; Ojong, Ojong E.; Taiwo, Ademiluyi Falilat; Zulkifli, Mohammad Fakhratul Ridwan; Daoudi, Walid; Wan Nik, Wan Mohd Norsani (Asia-Pacific Journal of Science and Technology, 2024)
The drying kinetics of Codiaeum Variegatum Brilliantissima-Zanzibar (Wire Croton) in the open air were modelled in this research. Daily temperature and the humidity of the environment were monitored every 12 hrs during the experiment. Wire Croton drying results obtained every 12 hrs were plotted against drying time to study the drying properties of the sample at 12 and 24-hr intervals. The results obtained were fitted into Lewis, Page, Modified Page, Handerson-Pabis and Ademiluyi’s model for the determination of the Root Mean Square Error (RMSE), which gave values of 0.277, 0.115, 0.173, 0.163 and 0.170, respectively and the coefficient of regression (R2) values of 0.539, 0.525, 0.954, 0.539 and 0.954, respectively for 12 hourly test. The 24-hour interval test gave RMSE values of 0.218, 0.113, 0.101, 0.162 and 0.097, corresponding R2 values of 0.801, 0.448, 0.448, 0.801 and 0.851. The Izionworu & Ojong model was developed and tested. When compared with existing models, Izionworu & Ojong’s thin-layer model gives the least RMSE value of 0.104 and 0.029 at 12 and 24-hour intervals respectively, compared to the other models and an R2 of 0.988 and 0.918 correspondingly for both the 12 and 24 hrs drying intervals. A 50% error deviation was achieved when the Izionworu & Ojong model was compared with the other two-term models confirming that the drying characteristics of wire croton in the open air are best described by the Izionworu & Ojong model.